Mental Health and Handgrip Strength Among Older Adults: A Nationwide Study - Yeunhee Kwak PhD; Yoonjung Kim PhD (SAGE Publishing, 2022)
Handgrip strength is used as an important indicator of health in older adults. We aimed to explore the association between stress, depression, and suicidal ideation and handgrip strength among older adults. We conducted this cross-sectional study involving 1254 individuals (aged ≥65 years), using data from the 2015 Korean National Health and Nutrition Examination Survey VI. We used logistic regression analysis to examine associations between handgrip strength and mental health. Among mental health factors, a significant difference was noted between stress and handgrip strength among the older adults. After adjusting for confounding factors, the odd ratio (OR) of stress among older adults with low handgrip strength was statistically significant in Models 1 (1.61 (95% CI: 1.01-2.57)) and 2 (1.59 (95% CI: 1.01-2.52)) but not in Model 3 (1.52 (95% CI: .96-2.43)). No significant association was found between depression or suicidal ideation and handgrip strength. The risk of stress was 1.59-1.61 times higher in older adults with low handgrip strength, compared to that in older adults with normal handgrip strength. It is necessary to develop strategies aimed at managing stress among older adults with low handgrip strength and educating them about the importance of handgrip strength and exercises that increase handgrip strength.